2010
DOI: 10.1021/ef101404k
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Bitumen−Silica and Oil−Silica Interactions in Ionic Liquids

Abstract: Previous work in this laboratory has shown that bitumen and oil can be readily separated from sand, using ionic liquids at ambient temperatures. To probe the mechanism underlying the relative ease of separation, atomic force microscopy (AFM) has been used to study interaction forces and adhesion between bitumen surfaces and a silica probe in the presence of liquid media. The energy of adhesion between bitumen samples obtained from both Canadian and U.S. oil sands are approximately an order of magnitude smaller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
84
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 46 publications
6
84
1
Order By: Relevance
“…Confined between tightly packed particles (in bridges), the IL would have interacted with many surfaces may have assumed an ordered structure. Recent AFM studies have indicated that this layering phenomenon is important in IL-particle interactions [45]. The existence of such a structure would also enhance the stability of the inter-droplet bridges.…”
Section: Region I Region Iimentioning
confidence: 98%
“…Confined between tightly packed particles (in bridges), the IL would have interacted with many surfaces may have assumed an ordered structure. Recent AFM studies have indicated that this layering phenomenon is important in IL-particle interactions [45]. The existence of such a structure would also enhance the stability of the inter-droplet bridges.…”
Section: Region I Region Iimentioning
confidence: 98%
“…However, its capabilities in acting in as a surface agent between bitumen and sand. Hogshead et al (2011) investigated with an atomic force microscopie the forces between bitumen and silica with 1-butyl-2,3-dimethylimidazolium tetrafluoroborate ([BMMIM BF 4 ]) and observed a reduction in adhesion by using the ionic liquid. Also, Babadagli (2016, 2017) proved the wettability modification of BMMIM BF 4 to a less oil wet surface at different temperatures (25°C, 90°C, and 180°C) and the improvement of gravity force by the chemical agent sodium metaborate (NaBO2).…”
Section: Chemicalsmentioning
confidence: 99%
“…Compared to other commercial chemicals, ionic liquids have many advantages such as their commercial availability, solvent stability, non-corrosiveness, recyclability, and low toxicity [10]. Many studies presented the extraction of more than 90% of bitumen from oil sand by using several IL (imidazolium base) mixed with non-polar solvents [11] [14]. Moreover, increasing ILs concentration in salt water resulted in an increase in oil recovery factor from sandstone and carbonate reservoirs [15].…”
Section: Introductionmentioning
confidence: 99%